Estimation of Vitamin C Status Among University Students During COVID-19 Pandemic (Medical Forum Monthly, 2023)
Objective: Vitamin C is known as a powerful antioxidant and immune booster vitamin. During the period of the rise in COVID-19 infections, it was medically advised to consume a sufficient amount of vitamin C. This study was very essential to estimate the status of Vitamin C among University Students during the peak period of COVID-19 infections.Study Design: Cross-Sectional Descriptive StudyPlace and Duration of Study: This study was conducted at the University of Sindh from December 2020 to February 2021.Materials and Methods: There were a total of 232 randomly selected male and female university students during the research work. The data was statistically calculated in percent and frequencies by using SPSS software version 21. The statistical difference was determined by applying a t-test and the P- value of < 0.05 was set as significant.Results: Only about 5-9% of male and female university students were consuming a moderate amount of vitamin C-rich food every day whereas, the majority were not taking vitamin C-enriched foods or citrus fruits in their diet. Only 9% of males and 14% of females were taking vitamin C supplements. 56% of females reported bleeding gums issue and 34% of males also reported teeth sensitivity with bleeding gums. Skin discoloration was not found in most of the cases (> 90%). About 47% of females and 37% of males were susceptible to COVID-19 infection due to their critical plasma vitamin C levels < 0.3 mg/dl.Conclusion: Both male and female university students were susceptible to COVID-19 infection due to their critically low levels of Plasma vitamin C. Females were more prone to COVID-19 infections compared to males due to their lower intake of vitamin C-rich foods and supplements. The male and female students of the university were found to lack sufficient intake of vitamin C. There were more females than males who reported bleeding gum issues. The students at the University level must be well aware of the immune-supportive, antiviral, and anti-inflammatory role of vitamin C.